Strategic relationship training to promote self-growth of the individual - علي, محمد حسين; لعيبي, لمياء رحيم (Journal of Economics and Administrative Sciences, 2019)
The main objective of the research is to identify the role of strategic training and its effect on enhancing the self-growth of the individual. Stratigic training represents a contemporary tendency. that is adopted by business organizations in carrying out their activities and tasks.It is worth to mention, that self-growth of the individual is one of the indictors used to determine the ability of organization to a achieve its goals.  The problem of the research has pointed out to the minimum awareness of the important role played by training strategy in enhancing the self-growth of the individual. The researcher has adopted an analytical approach, in collecting and analyses the research data in order to treat its problem. Therefore, the questionnaire has been used as a major tool for collecting the research data. It is based on a number of ready –made measurements. After it has been examined by tests of honesty and constancy to suit the search's targets which includes 42 paragraphs distributed to a group of 100 workers who work in Ministry of Industry and Minerals, Military industries Department. The workers are tested in a simple random sample method.The research depends on the statistical program (SPSS) in analysis of data, analysis of the link relationships and the effect between variables. The statistical tools are used in this field shown a number of results, most notably is the strategy of training plays a statistical important moral role, in enhancing the self-growth. This research recommends that organizations promote the self-growth of an individual in order to enable them the applications of strategy training, implementing their task and activities effectively. Which in return, will contribute in enhancing self-growth of the individual towards the organization.